Governança corporativa e a velocidade de ajuste da estrutura de capital das empresas brasileiras - Zappa, Pedro Albuquerque (2011)
This study aims to examine the relationship between corporate governance and the speed of adjustment to the optimal capital structure of companies listed on BM&FBovespa between 1998 and 2009, from the perspective of the Dynamic Trade-Off Theory. The level of corporate governance was measured on the basis of different listing segments of the BM&FBovespa, with some control variables used to determine the optimal leverage. The results indicate that firms with better governance have lower degree of leverage and adjust more quickly towards the optimum.